The Effect of Zinc oxide Nanoparticles (ZnO NPs) on the Viability of Leishmania tropic In Vitro - Gharby, Meaad A.; Al-Qadhi , Ban N. (Iraqi Journal of Science, 2022)
Cutaneous leishmaniasis (CL) also known under local names like (tropical sore, oriental sore and Baghdad sore) is the most common form of leishmaniasis. It is a public health and a social problem in many developing countries. The Old World disease primarily is caused by Leishmania major in dry desert areas and Leishmania tropica in urban areas. Recently, metal oxide nanoparticales have been versatile platforms for biomedical applications and therapeutic interventions. There is an urgent need to develop new types of antileishmanial agents instead of classical drug (pentostam), especially, when its efficacy showed a decline towards some strains of Leishmania. Therefore, the present work was aimed to evaluating antileishmanial activity of zinc oxide nanoparticles (ZnO NPs) on metabolic activity (viability) of Leishmania tropica parasites in both phases (promastigote and amastigote) in vitro condition. This study revealed the effects of different concentrations (2, 2.5, 3, 3.5, 4, 4.5 and 5μg/ ml) of ZnO NPs and pentostam drugs on L. tropica promastigote viability, which was recorded the maximum cytotoxic effect (25.12 ±1.47 and 40.81± 1.47) % at high concentration (5 μg/ml) for ZnO and pentostam respectively after 72 hr. The IC50 was calculated depending on the results of MTT assay to determine the most effective concentrations of ZnO NPs on the viability of L. tropica promastigotes. The result was 4.318 μg/ ml after 72 hr., while pentostam drug recorded an IC50 value only after 72 hr. which was 4.897 μg/ ml. On the other hand, the study also showed the effects of ZnO on amastigote phase, and the viability decreased by increasing the concentrations and incubation time. So the highest concentration (5 μg/ ml) recorded lower percentage of viability (18.17 ± 0.60 and 36.07 ± 2.68) % for ZnO NPs and pentostam respectively after 72 hr., while the IC50 of the results of MTT assay for both ZnO NPs and pentostam drug was 3.84 μg/ ml and 4.734 μg/ ml respectively after 72 hr.